TSH Receptor Signaling Abrogation by a Novel Small Molecule - Latif, Rauf; Realubit, Ronald B.; Karan, Charles; Mezei, Mihaly; Davies, Terry F. (Frontiers in Endocrinology, 2016)
Pathological activation of the thyroid stimulating hormone receptor (TSHR) is caused by thyroid stimulating antibodies in patients with Graves’ disease or by somatic and rare genomic mutations that enhance constitutive activation of the receptor influencing both G protein and non-G protein signaling. Potential selective small molecule antagonists represent novel therapeutic compounds for abrogation of such abnormal TSHR signaling. In this study we describe the identification and in-vitro characterization of a novel small molecule antagonist by high-throughput screening (HTS). The identification of the TSHR antagonist was performed using a transcription-based TSH inhibition bioassay. TSHR expressing CHO cells which also expressed a luciferase tagged CRE response element were optimized using bovine TSH as the activator in a 384 well plate format which had a Z score of 0.3-0.6. Using this HTS assay we screened a diverse library of ~80,000 compounds at a final concentration of 16.7μM. The selection criteria for a positive hit were based on a mean signal threshold of 50% inhibition of control TSH stimulation. The screening resulted in 450 positive hits giving a hit ratio of 0.56%. A secondary confirmation screen against TSH and forskolin - a post receptor activator of adenylyl cyclase – confirmed one TSHR-specific candidate antagonist molecule (named VA-K-14). This lead molecule had an IC50 of 12.3µM and a unique chemical structure. A parallel analysis for cell viability indicated that the lead inhibitor was non-cytotoxic at its effective concentrations. In-silico docking studies performed using a TSHR transmembrane model showed the hydrophobic contact locations and the possible mode of inhibition of TSHR signaling. Furthermore, this molecule was capable of inhibiting TSHR stimulation by Graves’ disease patient sera and monoclonal stimulating TSHR antibodies. In conclusion, we report the identification of a novel small molecule TSHR inhibitor which has the potential to be developed as a therapeutic antagonist for abrogation of TSHR signaling by TSHR autoantibodies in Graves’ disease.